Retrospective epidemiological analysis of SARS-CoV-2 wastewater surveillance and case notifications data – New South Wales, Australia, 2020. (18th October 2021) - Camphor, H. S.; Nielsen, S.; Bradford-Hartke, Z.; Wall, K.; Broome, R.
Abstract: This epidemiological study analysed SARS-CoV-2 wastewater surveillance and case notifications data to inform evidence-based public health action in NSW. We investigated measures of association between SARS-CoV-2 RNA fragments detected in wastewater samples ( n = 100) and case notifications ( n = 1, 367, as rates per 100, 000 population) within wastewater catchment areas ( n = 6); and evaluated the performance of wastewater testing as a population-level diagnostic tool. Furthermore, we modelled SARS-CoV-2 RNA fragment detection in wastewater given the case notification rate using logistic regression. The odds of a viral detection in wastewater samples increased by a factor of 5.68 (95% CI: 1.51–32.1, P = 0.004) with rates of one or more notified cases within a catchment. The diagnostic specificity of wastewater viral detection results was 0.88 (95% CI: 0.69–0.97); the overall diagnostic sensitivity was 0.44 (95% CI: 0.33–0.56). The probability of a viral detection result in wastewater exceeded 50% (95% CI: 36–64%) once the case rate within a catchment exceeded 10.5. Observed results suggest that in a low prevalence setting, wastewater viral detections are a more reliable indicator of the presence of recent virus shedding cases in a catchment, than non-detect results are of the absence of cases in a catchment. HIGHLIGHTS: Research was undertaken to investigate SARS-CoV-2 wastewater surveillance findings in relation to observed COVID-19 case notifications data in NSW, Australia. In a low prevalence setting such as in NSW, wastewater viral detections, particularly in catchments with no recent case notifications should trigger prompt public health action to rule out low-level virus circulation or undetected community transmission.